125 Definitive histological evidence of myocardial fibrosis in primary degenerative mitral regurgitation: causation of symptoms?. (May 2019) - Liu, Boyang; Neil, Desley; Premchand, Monisha; Bhabra, Moninder; Patel, Ramesh; Barker, Thomas; Billing, Stephen; Nikolaidis, Nicolas; Edwards, Nicola; Steeds, Rick
Abstract : Chronic primary mitral regurgitation (MR) exposes the left ventricle (LV) with a volume load that leads to progressive compensatory adjustments; initially LV enlargement and eccentric hypertrophy to progressive structural and functional damage. Identifying the deleterious stages of LV remodelling before the onset of irreversible dysfunction is critical to patient management and prognosis. Myocardial fibrosis with MR is proposed to develop in response to increased wall stress, but data are limited to small echo based imaging biomarkers. The aim of this prospective multi-centre study is to characterise the histological status of patients with chronic primary MR and examine associated changes in cardiac structure, function and symptom burden. 120 patients with primary degenerative MR (67% asymptomatic) were recruited prospectively. Coronary disease was excluded by angiography. All subjects underwent clinical assessment, multiparametric cardiac magnetic resonance (CMR) imaging, symptom assessment with the Minnesota Living with Heart Failure Questionnaire (MLHFQ) and cardiopulmonary exercise testing (CPET). 106 patients were referred for mitral valve surgery with the aim of collecting 3 LV biopsies per patient. Control myocardial samples were obtained from autopsies of 8 subjects who died of non-cardiac causes without signs of macroscopic or microscopic cardiac lesions. Due to feasibility, 237 LV biopsies were collected from 85 patients. Mean collagen volume fraction (CVFmean) was elevated in MR patients compared to controls (16.1±10.1% vs, 4.3±2.7%, P=0.002), with significant CVF burden present even in the asymptomatic cohort (14.7±9.2%). Pattern of fibrosis varied between diffuse interstitial fibrosis, coarse replacement fibrosis and endocardial thickening within and between each individual biopsy sample. Histological quantification of muscle hypertrophy demonstrated an increase in myofiber cross-sectional area in MR patients compared to controls but did not differ between asymptomatic and symptomatic patients. There was no relationship between CVF and age, gender, ventricular volumes, measures of MR severity, LVEF or extracellular volume (ECV). Late gadolinium enhancement, present in 34% of patients, was not predictive of higher CVFmean (15.3±9.0% vs 16.5±10.8%, P=0.63). CVFmean was higher in patients with Barlow's disease compared to FED (14±8% vs 10±11%, P=0.029) despite no difference in LV volumes, LVEF and MR severity. Symptom burden was associated with the extent of fibrosis (MLHFQ and CVFmean, R=0.25, P=0.03), and ECV (R=0.19, P=0.06). In a multivariable regression model, increasing CVFmean and ECV both independently predicted more advanced symptoms. In summary patients with chronic primary degenerative MR myocardial fibrosis and myofiber hypertrophy increased when still asymptomatic. t. With symptomatic MR there were further increases in CVF and ECV expansion, without continued muscle hypertrophy, suggesting that an imbalance in the fibrosis:muscle ratio may be contributory to the development of symptoms. See Figure 1 and Figure 2. Conflict of Interest: None